2017
DOI: 10.1016/j.rpor.2016.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of reproducibility of tumor repositioning during multiple breathing cycles for liver stereotactic body radiotherapy treatment

Abstract: a b s t r a c tAim: To evaluate the tumor repositioning during gated volumetric modulated arc therapy (VMAT) for liver stereotactic body radiotherapy(SBRT) treatment using implanted fiducial markers and intrafraction kilovoltage (kV) images acquired during dose delivery. Materials and methods:Since 2012, 47 liver cancer patients with implanted fiducial markers were treated using the gated VMAT technique with a Varian Truebeam STx linear accelerator.The fiducial markers were implanted inside or close to the tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
2
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 24 publications
0
17
2
3
Order By: Relevance
“…al. [13]used a KV plain lm to acquire the end-expiratory image to analyse the patient's intra-fraction errors and found that the 99% intra-fraction error in the SI direction was within 5 mm, which was smaller than in our study. However, the images were collected before the treatment beam was on, and the acquisition time was limited, which cannot represent intrafraction errors.…”
Section: Discussioncontrasting
confidence: 65%
See 3 more Smart Citations
“…al. [13]used a KV plain lm to acquire the end-expiratory image to analyse the patient's intra-fraction errors and found that the 99% intra-fraction error in the SI direction was within 5 mm, which was smaller than in our study. However, the images were collected before the treatment beam was on, and the acquisition time was limited, which cannot represent intrafraction errors.…”
Section: Discussioncontrasting
confidence: 65%
“…Markus Oechsner reported [16]that AIP is more suitable for 3D CBCT than MIP. Bedos L et al also believed that [13] CBCT was an average image and that registration with the planned AIP image can represent the patient's breathing pattern, so we used AIP as the reference image for registration with 3D CBCT images for liver SBRT. In the inter-and intra-fraction CBCT, the liver contour can be clearly displayed (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The geometric miss occurs due to a wrong detection of targets' positions, and this decreases dose coverage for tumors. 17 Moreover, a wrong detection of tumor positions in ABH may significantly increase treatment time as the ABH system does not allow to deliver irradiation without the images, which indicate that markers' positions were correct. [14][15][16] The aim of this study is to investigate the detectability of fiducial markers' positions for real-time target tracking systems, which are equipping with a standard linac.…”
Section: Introductionmentioning
confidence: 99%